Chinese consumer preferences and willingness to pay for carbon-labeled eggs: an analysis based on choice experiment method - Liu, Miaoling (Frontiers in Sustainable Food Systems, 2025)
This study aimed to investigate Chinese consumer preferences and willingness to pay for carbon-labeled eggs, and to explore the heterogeneity of consumer preferences and willingness to pay under different information interventions. A choice experiment was conducted to investigate consumer preferences for food quality attributes, and the survey data was analyzed utilizing a mixed logit model. The findings revealed that Chinese consumers prioritize eggs with organic certification and antibiotics-free labels. Additionally, Chinese consumers exhibit a positive willingness to pay for carbon-labeled eggs, however, the attribute of carbon labels is perceived as the least important among all attributes by consumers. In addition, the preference for carbon-labeled eggs exhibits heterogeneity, with female and young consumers demonstrating a greater willingness to pay a premium. The provision of information regarding global warming and the significance of carbon labels enhances consumers’ inclination to pay a premium for products with carbon labels.